Engaging interested parties to optimize wildfire smoke communication in Canada: challenges with initiating change - Choy, Amelia; Shellington, Erin M.; Rideout, Karen; Roushorne, Meghan; Joshi, Phalgun; Carlsten, Christopher (Frontiers in Public Health, 2023)
Background In February 2022, an online Wildfire Smoke Communication Workshop series identified priorities and strategies to improve wildfire smoke communication in Canada. We evaluated the engagement methods, the workshop series and workshop summary report, to determine if participants/organizations initiated changes identified in the workshop to optimize wildfire smoke communication plans. Methods Three evaluation surveys were developed using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework dimensions and PRISM (Practical, Robust, Implementation, and Sustainability Model) contextual domains to measure the engagement impact. Surveys 1, 2, and 3 were disseminated to workshop participants between February 2022 (post-workshop series), May 2022 (pre-wildfire season), and September 2022 (post-wildfire season). Likert survey responses were analyzed descriptively using means and standard deviations. Open-ended written responses were analyzed using deductive reasoning and response proportions. Results Of 69 workshop participants, 28, 19, and 13 responded to surveys 1, 2, and 3, respectively. Workshop participation helped survey 1 respondents consider optimizing wildfire smoke communication (M = 3.93, SD = 0.88). Workshop participation and the summary report helped survey 2 respondents consider new actions to optimize wildfire smoke communication (M = 3.84, SD = 0.74). The most intended action in survey 2 (68%, n = 13) and the most common action taken in survey 3 (62%, n = 8) was to simplify message content. The primary limitation to optimization was capacity. Conclusion The engagement methods, particularly the summary report, were beneficial for organizations to take action to optimize wildfire smoke communication in Canada. Future engagement methods should examine persisting system-level issues and capacity limitations as they undermine the ability to optimize wildfire smoke communication in Canada.